From "Euthanasia" to Sobibór: An SS Officer’s Photo Collection. Martin Cüppers Anne Lepper, and Jürgen Matthäus - Wilson, Hannah (Holocaust and genocide studies, 2024)
As we approach eighty-five years since the beginning of the Second World War, it is increasingly rare that discoveries of unseen, contemporaneous materials